Effects of wind and tree density on forest fire patterns in a mixed-tree species forest. Issue 1 (2nd January 2017) - Song, Hark-Soo; Lee, Sang-Hee
ABSTRACT: It is well known that global climate change causes an increase in forest fire frequency and severity. Thus, understanding fire dynamics is necessary to comprehend the mitigation of the negative effects of forest fires. Our objective was to inform how fire spreads in a simulated two-species forest with varying wind strengths. The forest in this study was comprised of two different tree species with varying probabilities of transferring fire that was randomly distributed in space at densities ( Ctot ) ranging from 0.0 (low) to 1.0 (high). We studied the distribution pattern of burnt trees by using local rules of the two-dimensional model. This model incorporated wind blowing from south to north with strength ( Pw ) ranging from 0.0 (low) to 1.0 (high). Simulation results showed that when Ctot > 0.45 the fire covered the entire forest, but when Ctot ≤ 0.45 the fire did not spread. The wind effect on the variation of the amount of the burnt tree was maximized at the critical density and dramatically decreased with increasing Ctot . Additionally, we found that the term of Ctot and Pw plays an important role in determining the distribution.